UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN BAWANG DAYAK (Eleutherine palmifolia Merr.) TERHADAP Escherichia coli - Eka Kumalasari; Dhea Agustina; Novia Ariani (Jurnal Insan Farmasi Indonesia, 2020)
Dayak onions plants are mostly found in Middle of Borneo area which Dayak ethnic used for medicinal plant. General the part is only the tubers while the leaves are often removed and rarely used. Dayak leeks contain alkaloids, flavonoids, saponins, and tannins. Based on the content of dayak scallions, it is suspected that the metabolite compound has activity in inhibiting the growth of Escherichia coli. The aim of the study was determine of inhibitory for antibacterial activity of extract dayak (Eleutherine palmifolia Merr.) against Escherichia coli. The extraction of dayak leeks was done by maseration method using ethanol 70%. Antibacterial activity test dayak leeks extract using disc diffusion method with any other concentrate. Positive control is Ceftriaxone and negative control is ethanol 96%. Tool that was used for measurement of inhibitory zone is calipers. The result of this test indicate extract dayak leeks have antibacterial activity against Escherichia coli on concentrate 100%, 80%, 60%, 40%, and 20% with average diameter of inhibitory zone are 21.88mm (to strong); 19.88mm (strong); 17.68mm (strong): 9.81mm (medium); 3.32mm (weak). The result of SPSS analysis indicate that each extract concentrate have a different significant result (P<0,000).